1998
DOI: 10.1006/viro.1998.9301
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD46 in Measles Virus Infection in CD46 Transgenic Mice

Abstract: The susceptibility of CD46 (human membrane cofactor protein) transgenic mice to measles virus (MV) infection was investigated. Cell cultures (lung and kidney) established from transgenic and control mice showed that although both could be infected only those from the CD46+ mice gave fusion. A complete round of replication with the release of infectious virus was detected exclusively in the transgenic cell cultures whose permissiveness to MV was markedly less than that of Vero cells. The ability of MV to replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…We then performed a comparative examination of MCP (CD46) expression in the three independently derived strains. This comparison did not include a fourth strain generated using a 80-kb genomic fragment [38]. We found that MCP (CD46) was expressed on all cells and tissues analysed.…”
Section: Discussionmentioning
confidence: 96%
“…We then performed a comparative examination of MCP (CD46) expression in the three independently derived strains. This comparison did not include a fourth strain generated using a 80-kb genomic fragment [38]. We found that MCP (CD46) was expressed on all cells and tissues analysed.…”
Section: Discussionmentioning
confidence: 96%
“…It should also have applications in the development of recombinant MV vaccines (19,20,31) and studying the oncolytic properties of this virus (21,22,32). Other groups have generated mice that express human CD46, which is the receptor used by vaccine and laboratory adapted strains of MV for virus entry (2)(3)(4)(5)(6)33). These labs reported transient MV infections in these mice with limited virus production due to the induction of innate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…MIBE is observed in immunosupressed patients, for example, in some of those with human immunodeficiency virus type 1 infection and those undergoing immunosuppressive therapy. It has become more prevalent in recent years and leads to the death of the individual within a few weeks.Two approaches have been used to study MV neurotropism in efforts to generate a small-animal model for CNS infection.First, following the identification of the complement cofactor CD46 as a receptor for the Edmonston strain of MV (11, 30) a number of groups have produced transgenic animals which express the receptor (6,16,28,29,32,34). The inflammatory response in the CNS of transgenic animals has been investigated.…”
mentioning
confidence: 99%
“…First, following the identification of the complement cofactor CD46 as a receptor for the Edmonston strain of MV (11,30) a number of groups have produced transgenic animals which express the receptor (6,16,28,29,32,34). The inflammatory response in the CNS of transgenic animals has been investigated.…”
mentioning
confidence: 99%